The Effect of Work Culture, Training, and Employee Placement on Employee Performance: PT Bank Perekonomian Rakyat Sumatera Selatan - Hendera, Hendera; Rahayu, Sri; Tobari, Tobari (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine the effect of work culture, training, and employee placement on employee performance in PT. Bank Perekonomian Rakyat Sumatera Selatan. This type of research is Associative. The variables used by the researcher are Work Culture, Training, Employee Placement, and Employee Performance. The sample in this study was 128 Employees of PT. Bank Perekonomian Rakyat Sumatera Selatan selected by Cluster Random Sampling. The primary data used in this study was collected through a questionnaire. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that (1) Work Culture, Training, and Employee Placement together have a positive and significant effect on Employee Performance, and (2) Work Culture has a positive but insignificant effect on Employee Performance. (3) Training has a positive and significant effect on Employee Performance. (4) Employee Placement positively and significantly affects Employee Performance.